(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The paper presents the results of the technology for producing thermoelectric substances with the aim of creating highly efficient thermoelectric converters of thermal energy into electrical energy. Changes in the properties of low-temperature thermoelements depend on sample manufacturing methods. The technology for obtaining homogeneous samples with a given concentration of charge carriers, as well as the properties of pressed samples, are described.